Thyroid Function Tests and the Serum Levels of Prolactin in Women With Suicide Attempt - Rahmani, Farnaz; Rahmani, Farzad; Niafar, Mitra; Ostadi, Ali; Robai, Navideh; Abdollahi, Fariba; Asadollahi, Samira (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Suicide is a major public health concern across the world. Based on related studies, thyroid dysfunction is associated with psychiatric disorders. This study aimed to determine the relationship between thyroid function tests and serum prolactin in women with suicide attempt. Methods: A total of 261 women with the suicide attempt were included in this descriptive-analytical study which took over one year (July 2015- July 2016). In addition, the patients’ serum Thyroid-Stimulating Hormone (TSH), free T4, and prolactin were measured, too. Results: Of 261 patients, 44(16.9%) had subclinical hypothyroidism, 3(1.1%) clinical hypothyroidism, and 1(0.4%) hyperthyroidism. The median value of serum prolactin in the patients with decreased thyroid function was higher. There were not significant relationship between suicide attempts and thyroid dysfunction or serum level of prolactin. Conclusion: Although there was no significant relationship between thyroid test, serum level of prolactin and suicide attempts, the prevalence of thyroid dysfunction and high serum levels of prolactin were clinically significant in women who attempted suicide. Thus, the measurement of serum TSH, free T4 and serum levels of prolactin could be considered for these patients.